A first principles study of the distribution of iron in sphalerite - Wright, Kathleen; Gale, Julian (Pergamon-Elsevier Science Ltd, 2010)
Quantum mechanical techniques, based on density functional theory, have been used to study the distribution of iron impurities in sphalerite (ZnS) at compositions ranging from 3.125 to 12.5 mol% FeS. Our results show that iron is most easily incorporated by direct substitution onto the zinc site and that energies for solution reactions involving FeS are exothermic when the system is zinc deficient. Furthermore, there appears to be a small driving force for the formation of bound Fe? Fe pairs at low iron concentrations, though there is no particular preference found for larger clusters of iron. The influence of iron on the sphalerite cell parameter is shown to be sensitive to the presence of Fe-Fe pairs and to the degree of sample non-stoichiometry.